Randomized controlled trial for the effects of an exercise program for functional remission and weight control in schizophrenia: a community mental health study - ŞİŞMAN, FATMA NEVİN (My University, 2022)
This research was conducted to determine the effect of an exercise program on functional remission and weight control in schizophrenia. This experimental study was conducted with pre-posttests and a control group at community mental health centers with 32 individuals with schizophrenia. The individuals participating in the program registered a more significant increase on the functional remission levels compared to the control group and a significant difference was found between the pretest/posttest BMI measures of the experimental group. The nurse-led exercise program is an effective plan that can be used in achieving functional remission.
Keywords: Tıp; Sağlık Bilimleri; Hemşirelik; Medicine; Health Sciences; Nursing; HEMŞİRELİK; Klinik Tıp; Klinik Tıp (MED); Psikiyatri; NURSING; CLINICAL MEDICINE; Clinical Medicine (MED); PSYCHIATRY; Critical Care Nursing; Psychiatric Mental Health; Medical and Surgical Nursing; Pharmacology (nursing); Maternity and Midwifery; Oncology (nursing); Nursing (miscellaneous); Psychiatry and Mental Health; Advanced and Specialized Nursing; Nurse Assisting; LPN and LVN; General Nursing; Emergency Nursing